The status and role of ErbB receptors in human cancer - Uberall, I; Kolár, Z; Trojanec, R; Berkovcová, J; Hajdúch, M (Experimental and molecular pathology, 2008)
Changes in the expression of cellular receptors contribute to the progression of many types of solid tumors. In this review, we focus on the normal role of ErbB receptors as signal transducers and their contribution to carcinogenesis when there are abnormalities in ErbB signaling due to the overactivity of the receptors or the overexpression of ligands, which can lead to developmental defects and have been associated with many types of cancers.
Keywords: myši; Neoplasms; Biomarkers, Tumor; signální transdukce; mužské pohlaví; Signal Transduction; ErbB Receptors; ženské pohlaví; nádorové biomarkery; zvířata; Humans; Mice; lidé; Female; nádory; erbB receptory; Male; Animals